Sequence optimization in a sequencing batch reactor for biological nutrient removal from domestic wastewater - Debik, Eyup; Manav, Neslihan (SPRINGER, 2010)
The purpose of this work was to determine optimum sequence retention times for nutrient removal with low-cost using very short aeration time in an SBR treating domestic wastewater. During the study, four different CYCLEs were evaluated, with the highest removal efficiencies recorded for the CYCLE with fill, anaerobic, aerobic1, anoxic, aerobic2, settle, and decant sequences operated at retention times of 0.5, 2, 2, 1, 0.75, 1, and 0.5 h, respectively. For this CYCLE, the removal efficiencies of chemical oxygen demand (COD), total Kjeldahl nitrogen (TKN), ammonia nitrogen (NH(3)-N), total phosphorus (TP), and ortho-phosphate (PO(4)-P) were found, on average, to be 91, 78, 85, 87, and 83%, respectively. The optimum sequence retention time was determined via the analysis of variance (ANOVA) using the Matlab software (Mathworks Inc.). The data indicated that the total time of the aerobic sequences was shorter than those of previous studies for similar level of removal efficiencies in all parameters including N and P.
Keywords: Sequencing batch reactor (SBR); Nutrient removal; Domestic wastewater; ANOVA; REAL-TIME CONTROL; NITROGEN REMOVAL; PHOSPHORUS REMOVAL; CONTROL STRATEGY; DENITRIFICATION; SYSTEM; SBR; NITRIFICATION; PERFORMANCE; ENHANCE; Biotechnology & Applied Microbiology; Engineering